THE PROCESS OF IDENTITY CONSTRUCTION OF BUDDHIST TOURIST SITES IN CHIANG RAI - Pabhassaro, Pramaha Setthasiri; Vichai, Virot; Kotsupho, Phisit (Journal of MCU Nakhondhat, 2021)
This article is part of a dissertation concerning the process of identity construction of Buddhist learning centers and Buddhist tourist sites in Chiang Rai province. The objective is to analyze the process of identity construction in Buddhist tourist sites by examining 10 of Chiang Rai’s prominent Buddhist learning centers, which consist of Wat Rong Khun, Wat Huay Pla Kang, Wat Sang Kaew Phothiyan, Wat Phra That Pha Ngao, Wat Rong Suea Ten, Cherntawan International Meditation Center, Wat Phra That Doi Tung, Wat Phra Sing, Wat Phra Kaew, and Wat Chiang Yeun. The study was conducted using field research method, with data collected through in - depth interviews of 130 main respondents, which included 30 abbots/monks/lay personnel and 100 tourists, for each interviewer. These data were then used to analyze the concept of identity construction employed among the 10 sample groups. As a result, the findings revealed two different types of identity construction process utilized by Buddhist learning centers in Chiang Rai. 1) Buddhist learning center which was a temple with established religious significance before it was developed into tourist site. Built according to traditional concept of temple which has been to serve the local community, this type of learning center rely on word - of - mouth publicity, while Buddhist monks, together with members of local community, are responsible for its daily upkeep. 2) Contemporary Buddhist learning center built in the era when temple also functions as tourist site. This type of learning center is built to meet international standards and meant to serve people from around the world. Publicity are done mainly by utilizing media technology, while staffs employed by the foundation or company which oversees the site are responsible for its maintenance.